Combination of 5-aminosalicylic acid and hyperthermia synergistically enhances apoptotic cell death in HSC-3 cells due to intracellular nitric oxide/peroxynitrite generation. (1st June 2019) - Moniruzzaman, Rohan; Rehman, Mati Ur; Zhao, Qing-Li; Jawaid, Paras; Mitsuhashi, Yohei; Sakurai, Kotaro; Heshiki, Wataru; Ogawa, Ryohei; Tomihara, Kei; Saitoh, Jun-ichi; Noguchi, Kyo; Kondo, Takashi; et al.
Abstract: The repurposing of existing FDA-approved non-cancer drugs is a potential source of new treatment options for cancer patients. An anti-inflammatory drug, 5-aminosalicylic acid (5-ASA), has been clinically used to treat inflammatory bowel disease. Hyperthermia (HT) is widely applicable addendum therapy with the existing cancer treatment modalities. Here, we addressed how 5-ASA combined with HT induces lethal effects in human oral squamous cell carcinoma (OSCC) HSC-3 cells. We found that 5-ASA/HT combination significantly inhibited the viability of HSC-3 cells, while cytotoxic effects in primary human dermal fibroblast cells were minor. Apoptotic endpoints were significantly increased by the 5-ASA/HT combined treatment, as evidenced by presence of Annexin V-FITC/PI positive cells, loss of MMP, Bcl-2/Bax ratio alteration, and increased Fas, cleaved Bid, and caspase expression. Interestingly, the enhancement of apoptosis was reversed in the presence of ON/ONOO − scavengers. These findings indicate that the combination treatment enhances apoptosis via ON/ONOO − mediated ER stress-Ca 2+ -mitochondria signaling and caspase-dependent apoptotic pathways. Our findings provide novel evidence that the combination of 5-ASA and HT is a promising approach for the enhancement of apoptosis; it may serve as an effective strategy for treating human OSCC. Highlights: Anti-inflammatory agent 5-ASA is a potent thermo-sensitizer. 5-ASA with HT enhances intracellular NO generation and subsequent reacts with . O2 − to form ONOO − . 5-ASA/HT co-treatment enhances apoptosis via intrinsic and extrinsic apoptotic pathway. ER stress-Ca 2+ mediated pathway also contribute to the enhancement of apoptosis. The combination of 5-ASA with HT might be a potential therapeutic strategy for OSCC.